Implementation of the Omnibus Law: Legislative Impact and Consequences - Jefri, Jefri; Rustan, Ahmad; Ichlas, Rudy Iskandar (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The Implementation of the Omnibus Law in Indonesia through Law Number 11 of 2020 on Job Creation represents a significant step in regulatory reform, encompassing various sectors. This law aims to streamline regulations, enhance investment, and create job opportunities. This study seeks to analyze the impact and implications of the Omnibus Law on legislative politics in Indonesia. Using a qualitative approach and various theoretical frameworks from the fields of law, economics, politics, and sociology, this research examines regulatory changes, legislative processes, and the social, economic, and environmental impacts of the Omnibus Law's implementation. The findings indicate that while the Omnibus Law has the potential to improve the investment climate and economic growth, concerns exist regarding the reduction of workers' rights, negative environmental impacts, and the lack of public participation in the legislative process. The implications for legislative politics include changes in the relationship between central and regional governments, as well as political dynamics at the national and local levels. It is crucial for the government to ensure transparent, accountable, and participatory implementation to achieve sustainable development goals and improve the welfare of the Indonesian people.